1045 Summarising the Reporting of Regulatory Procedures in Robotic Cholecystectomy: A Systematic Review and Narrative Synthesis. (12th October 2021) - Higginbotham, G; Gull, E; Henshall, D; Handa, I; Brewster, O; Jones, C S; Kirkham, E N; ,
Abstract: Introduction: Robotic cholecystectomy (RC) represents the most recent innovation in the management of gallstones. Whilst RC is becoming increasingly widespread, the evidence base surrounding its introduction has not been characterised. When evaluating innovative surgical techniques, adherence to regulatory and governance procedures is essential in maintaining patient safety. This study aims to appraise the reporting of studies of RC, focussing on regulatory procedures. Method: Systematic searches identified all published studies reporting RC. Data collection was based on the IDEAL (Idea, Development, Exploration, Assessment, Long-term follow-up) framework, and included general study characteristics, governance approvals, trial registration, study funding, conflicts of interests, and information communicated to patients. Results: Systematic searches identified 1425 abstracts. Of the 90 full-text papers included, only three were randomised controlled trials. The majority (71%) were single-centre studies. Conflicts of interest were common, with 11 (12%) studies funded by the robot manufacturer, and 23 (26%) reporting conflicts related to authors. Ethical approval was confirmed in 51 (57%) studies; four reported prior registration with a register. Only forty-two studies (47%) documented obtaining patient consent for study participation. Only four documented discussions regarding the innovative nature of RC. In ten, modifications to the robot or technique were described, but it was not apparent if patients were informed of these. Conclusions: This comprehensive review highlights multiple deficiencies in the reporting of regulatory procedures in the evaluation of RC. Improved reporting is required in studies of RC to ensure transparency, interpretability, and the safe, evidence-based adoption of new technologies into clinical practice.